Pairing structural reconstruction with catalytic competence to evaluate the mechanisms of key enzymes in the folate‐mediated one‐carbon pathway - Zhao, Li Na; Kaldis, Philipp (The FEBS journal, 2023)
Mammalian metabolism comprises a series of interlinking pathways that include two major cycles: the folate and methionine cycles. The folate‐mediated metabolic cycle uses several oxidation states of tetrahydrofolate to carry activated one‐carbon units to be readily used and interconverted within the cell. They are required for nucleotide synthesis, methylation and metabolism, and particularly for proliferation of cancer cells. Based on the latest progress in genome‐wide CRISPR loss‐of‐function viability screening of 789 cell lines, we focus on the most cancer‐dependent enzymes in this pathway, especially those that are hyperactivated in cancer, to provide new insight into the chemical basis for cancer drug development. Since the complete 3D structure of several of these enzymes of the one‐carbon pathway in their active form are not available, we used homology modelling integrated with the interpretation of the reaction mechanism. In addition, have reconstructed the most likely scenario for the reactions taking place paired with their catalytic competence that provides a testable framework for this pathway. The folate‐mediated metabolic cycle uses several oxidation states of tetrahydrofolate to carry activated one‐carbon units to be used and interconverted within cells, which are required for nucleotide synthesis, methylation and particularly for cancer cell proliferation. We used homology modelling integrated with interpretation of the reaction mechanism, and have reconstructed the most likely scenario for the reactions taking place paired with the catalytic competence of enzymes of the one‐carbon pathway.